2022
DOI: 10.3389/fphar.2022.952800
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of the Cytoprotective Activity of Micelles with DSPE-PEG-C60 as a Carrier Against Doxorubicin-Induced Cytotoxicity

Abstract: To deliver doxorubicin (DOX) with enhanced efficacy and safety in vivo, fullerenol-modified micelles were prepared with the amphiphilic polymer DSPE-PEG-C60 as a carrier, which was synthesized by linking C60(OH)22 with DSPE-PEG-NH2. Studies of its particle size, PDI, zeta potential, and encapsulation efficiency were performed. DOX was successfully loaded into the micelles, exhibiting a suitable particle size [97 nm, 211 nm, 260 nm, vector: DOX = 5:1, 10:1; 15:1 (W/W)], a negative zeta potential of around −30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many studies have reported that fullerenols exhibit protective effects against doxorubicin (DOX)-induced cardiotoxicity, hepatotoxicity and nephrotoxicity in rats subjected to high doses of DOX in vivo. The cytoprotective effects of fullerenols against doxorubicin (DOX)-induced damage in normal cells in vitro were also observed in our previous studies [17]. In the present study, an investigation was conducted to examine the antioxidant properties of C60(OH) 22 and its amphiphilic derivative DSPE-PEG-C60 in protecting normal HK-2 and L02 cells against cytotoxicity induced by NCTD.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Many studies have reported that fullerenols exhibit protective effects against doxorubicin (DOX)-induced cardiotoxicity, hepatotoxicity and nephrotoxicity in rats subjected to high doses of DOX in vivo. The cytoprotective effects of fullerenols against doxorubicin (DOX)-induced damage in normal cells in vitro were also observed in our previous studies [17]. In the present study, an investigation was conducted to examine the antioxidant properties of C60(OH) 22 and its amphiphilic derivative DSPE-PEG-C60 in protecting normal HK-2 and L02 cells against cytotoxicity induced by NCTD.…”
Section: Discussionsupporting
confidence: 65%
“…The findings indicated that the fullerenol (C60)-modified micelles demonstrated reduced cytotoxicity in normal cell lines (L02, H9c2, GES-1) in comparison to free DOX in vitro. The results also showed that micelles modified with C60 exhibited a reduction in intracellular ROS in the H9c2 cells in comparison to free DOX [17]. However, it is still uncertain whether fullerenol has the potential to play a role against the oxidative stress induced by other anticancer drugs in normal tissues.…”
Section: Introductionmentioning
confidence: 93%
“…Beihua et al 85 we could not consider the report as complete since the authors did not complete the investigation after sacrificing the animals.…”
Section: Frl As Potential Organ Protector In Oncology Treatmentsmentioning
confidence: 98%
“…The most significant research investigations related to the potential applicability of FRL as organ-protectors in oncology treatments are listed in Table 2. [11][12][13][14][15]19,20,22,24,[75][76][77][78][79][80][81][82][83][84][85] Our extended research team has been publishing several papers focusing on the applicability of FRLs as antioxidants to protect organs from the side effects of chemotherapy [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and radiotherapy. 11,77,82 Most of the tests were performed with intraperitoneal injection of FRL, [11][12][13][14][15][16][18][19]…”
Section: Frl As Potential Organ Protector In Oncology Treatmentsmentioning
confidence: 99%
“…MaterialType Refs PEG-DSPE PEG-lipid conjugate[61,62] PEG-DSPC PEG-lipid conjugate[61] PEG-PCL PEG-lipid conjugate[63,64] PEG-PE/PG/PS PEG-phospholipid conjugate[65,66] PEG-PLGA/PEG PEG-polymer conjugate[67] …”
mentioning
confidence: 99%